Complex and transdisciplinary analysis of the bolivian maritime enclaustration - Vera Quezada, Karina; Ariel Arce Conde, Dorian (Seven Editora, 2023)
Within the policies and strategies to seek a sovereign exit to the sea of Bolivia, from the dialogic perspective is the Historiology that becomes the strategic analysis of history that differs from the Historiography that deals with the historical chronology, for that reason In this article, an analysis from complexity is developed to make known about the policy and strategy that Bolivia should employ in the maritime issue, taking a complex and transdisciplinary perspective, analyzing the multidimensionality of options and therefore it can be said that, "Chile does not it is the only way in which Bolivia could converge to gain access to a port and maritime coasts ". For this reason, for the present analysis, according to (Cruz Barreiro, 2009) Morín explained that: it will be necessary to consider that the human being is at the same time physical, biological, psychological, cultural, social and historical and this complex unit of human nature that it is disintegrated and must be restored in such a way that from where it is, it becomes aware and conscious of its complex identity and its common identity to all other humans. Throughout the last decades, the conditions of international policy exposed by the state of Bolivia were more aggressive and had an impact at the international level, such is the case of the lawsuit before the Hague to force the Chilean state to negotiate that allow a sovereign exit to the Pacific Ocean. (Morin & Le Moigne, The intelligence of complexity Epistemology and Pragmatics, 2006) referred to the following: "As Pascal said, you have to conceive the circular relationship: you cannot know the parts if you do not know the whole, nor you can know the whole without knowing the parts. The notion of organization becomes capital because, through the reorganization of the parts into a whole, emergent qualities appear and inhibited ones disappear ". Then it will be necessary to reconnect this politics from multiple notions of order, disorder, organization and to recognize the problems of irreducibility and indeducibility of complex relationships existing between the parts and the whole to later unite the notion of unity with that of plurality or diversity and in this way, they come together in probable agreements. Because it does not have a state policy that integrates the different levels of leadership and power factors through a multidisciplinary defense with an integrated approach to the dimensions of power, the approach made by Bolivia was not adequate from what can be said. that, the court’s decision was not the expected one, which had an impact on social morality due to the expectations that had been created, therefore, this article makes a complex analysis from a multidimensional perspective, giving way to a way of knowledge capable of apprehending objects in their contexts and at the same time in a set, gathering and organizing dispersed knowledge and in this way showing the indissoluble union between unity and diversity and all that is human. DOI: 10.56238/pacfdnsv1-034